You are on page 1of 17

Brain Storming

Comprehensions UNIT 6
Linked Comprehension Type
C1. 1. Answer (1)
We observe that

1
∑a  ∑ 3
n n

Sn = a1 + a2 + a3 + ...+ an

1 1 1 1
=    ... 
2 3
3 3 3 3n

1 ⎛ n⎞
⎜1 – ⎛⎜ 1 ⎞⎟ ⎟
⎜ ⎡ ⎛ 1 ⎞n ⎤
3
⎝ ⎝ 3 ⎠ ⎟⎠ 1
⎢1 – ⎜ ⎟ ⎥
= = 2 ⎢ ⎝3⎠ ⎥
1 ⎣ ⎦
1–
3

1⎡ 1 ⎤ 1
lim Sn = ⎢1 – n ⎥ 
lim
n  2 ⎣ 3 ⎦ 2

1
 S= which is finite and definite
2

 The given series is convergent


2. Answer (2)
Here an = 4n
 Sn = a1 + a2 + a3 + ... + an–1 + an
= 4 + 42 + 43 + ... + 4n–1 + 4n

=

4 4n – 1
=
4 n 
4 –1  
4–1 3

4
 nlim lim ( 4 n  1) = 
  Sn = n 3

S = sum of the series is infinite.


 The given series under consideration is divergent.

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
776 Brain Storming Comprehensions Success Magnet (Solutions)

3. Answer (3)
We have
an = (– 1)n – 1
Sn = a1 + a2 + a3 + a4 + a5 + ...+ an–1 + an
= 1 – 1 + 1 – 1 + 1 ... + (–1)n–2 + (– 1)n–1
= 0 or 1 according as n is even or odd.

 lim Sn does not exist as Sn is either 0 or 1 according as n is even or odd.


n
 The given series is ∑ an is oscillatory.
C2. 1. Answer (1)
2. Answer (2)
3. Answer (1)
We have

1 1 1 1 1 1 1
∑n 2 = 1
2 2

3 2

4 2

5 2

6 2

72
 ... 

⎛ 1 1 ⎞ ⎛ 1 1 1 1 ⎞ ⎛ 1 1 1 1 ⎞
= 1  ⎜ 2  2 ⎟  ⎜ 2  2  2  2 ⎟  ⎜ 2  2  2  ...  2 ⎟ +.......
⎝2 3 ⎠ ⎝4 5 6 7 ⎠ ⎝8 9 10 15 ⎠

⎛ 1 1 ⎞ ⎛ 1 1 1 1 ⎞ ⎛ 1 1 1 ⎞
 1  ⎜ 2  2 ⎟  ⎜ 2  2  2  2 ⎟  ⎜ 2  2  ...  2 ⎟ +.......
⎝2 2 ⎠ ⎝4 4 4 4 ⎠ ⎝8 8 8 ⎠

1 1 1
= 1  2  3  ... ...
2 2 2

1
= = 2 = a finite number
1–1
2
1
 ∑n 2
is convergent

We have

1 1
 , n  N, n  1
n n
1 1 1 1 1
 ∑ n
 ∑n = 1   ...   ...
2 3 n
1
Which is a divergent series the given series ∑ n
, being greater than a divergent series is itself divergent.

Also

1 1 1 1 1 1
∑ – 1 n –1

n 2 = 1–
2 2

3 2

4 2

5 2

62
 ... to 

1 1 1 1 1
< 1 2
 2
 2
 2
  ...
2 3 4 5 62
a convergent series
1
 ∑ – 1 n –1

n2
is a convergent series.

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 777
C3. 1. Answer (1)
2. Answer (2)
3. Answer (3)
We have
a1 > 0, a2 > 0 a1 > a2

an + 1 = an an – 1 , n  2

For n = 2 a32 = a1 a2

 a3 is the G.M. between a1 and a2.


 a1 > a3 > a2, as a1 > a2
For n = 3,

a42 = a3a2

 a4 lies between a2 and a3


 a3 > a4 > a2, as a3 > a2
For n = 4

a52 = a3a4

 a5 is G.M. between a3 and a4


 a3 > a5 > a4, as a3 > a5
For n = 5

a62 = a4a5

 a5 > a6 > a4
Combining the above inequalities we get
a1 > a3 > a5 > a6 > a4 > a2
Continuing in this way we get
a1 > a3 > a5 > a7 > ...> a2n – 1 > a2n > a2n – 2 >...> a6 > a4 > a2
which shows that
{a2n–1} is monotonic decreasing sequence bounded below by a2
and {a2n} is monotonic increasing sequence bounded above by a1 hence they are convergent and converges
to limits l and l1 respectively, say
i.e. a2n + 1  l
a2n  l1 as n   .

2
Now a2n  1 = a2n a2n –1

Taking limit as n , we get


l 2 = ll1
 l = l1 as l  0
Hence the sequences {a2n} and {a2n + 1} converge to the same limit

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
778 Brain Storming Comprehensions Success Magnet (Solutions)

We observe that
2
an  1 = anan–1

2
 an  1 an = an2an –1

= an2–1 an – 2

= an2– 2 an – 3
............................
............................

= a22a1
Taking limit as n  , we get

lim an2  1 an = a22a1


n 

 l 3 = a22a1

 
1
 l = a a2 3
1 2

 
1
 nlim

an = a a 2 3
1 2

C4. 1. Answer (3)


2. Answer (1)
3. Answer (1)
We have
x – 1 x – 2 x – 3 x –  
y = f(x) = x –  
For x  , f(x) = (x – 1) (x – 2) (x – 3)
Let g(x) = (x – 1) (x – 2) (x – 3)
= x3 – 6x2 + 11x – 6

1 1
 g(x) = 3x2 – 12x + 11 = 0 gives x = 2  ,2–
3 3
We observe that

⎛ 1 ⎞ ⎛ 1 ⎞⎛ 1 ⎞⎛ 1 ⎞ 1 ⎛1 ⎞ –2
g ⎜⎜ 2  ⎟ = ⎜1 
⎟ ⎜
⎟⎜
⎟⎜
⎟ ⎜– 1
⎟⎜
⎟ =
⎟ ⎜ – 1⎟ =
⎝ 3⎠ ⎝ 3⎠⎝ 3⎠⎝ 3⎠ 3 ⎝3 ⎠ 3 3

⎛ 1 ⎞ ⎛ 1 ⎞⎛ 1 ⎞⎛ 1 ⎞ 1 ⎛ 1⎞ 2
and g ⎜⎜ 2 – ⎟ = ⎜1 –
⎟ ⎜
⎟ ⎜–
⎟⎜
⎟ ⎜– 1–
⎟⎜
⎟ =
⎟ ⎜1 – ⎟ 
⎝ 3⎠ ⎝ 3⎠⎝ 3⎠⎝ 3⎠ 3 ⎝ 3 ⎠ 3 3

–2 1
Thus (x – 1) (x – 2) (x – 3) = has 2  as twice repeated root. Let the third root be k1. Then
3 3 3
2
2 ⎛ 1 ⎞
(x – 1) (x – 2) (x – 3) + = ⎜⎜ x – 2 – ⎟
⎟ x – k 1 
3 3 ⎝ 3⎠

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 779

2
Equating the coefficient of x2 from both sides we get 6 = k1  4 
3

2
 k1 = 2 –
3

Also the equation

2 1
(x – 1) (x – 2) (x – 3) = has 2 – as twice repeated root. Let the third root be k2
3 3 3

2
⎛ 1 ⎞
2
Then (x – 1) (x – 2) (x – 3) – = ⎜⎜ x – 2  ⎟
⎟ x – k 2 
3 3 ⎝ 3⎠

2
On equating the coefficient of x2 from both sides we get k2 = 2 
3

1
2
k2 3
1 2–
1 2 3 k1
3

⎡ 2 2 ⎤
1. Since g(x) = (x – 1) (x – 2) (x – 3) is many one in [k1, k2] i.e. ⎢2 – ,2 ⎥ and if   [k1, k2] range
⎣ 3 3⎦
of f(x) is (– , )

1
We observe that g(x) has a maxima at x = 2 – , hence when f(x) has no local maximum value,
3

1
= 2–
3

C5. 1. Answer (1)


We have
f (x) = 3x2 – 12x + 9 = 3(x2 – 4x + 3) = 3(x – 1) (x – 3)
 f (x) = 0 gives x = 1, 3
We observe the sign of f (x)

x – 0 3 

Sign of
– ve + ve + ve + ve
f(x)

Which shows that only one variation of the sign of f(x) takes place and hence the given equation
x3 – 6x2 + 9x + 10 = 0 has exactly one real root.

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
780 Brain Storming Comprehensions Success Magnet (Solutions)

2. Answer (3)

Here f(x) = x3 – 6x2 + 9x – 2

 f (x) = 3x2 – 12x + 9 = 3(x2 – 4x + 3)

= 3(x – 1) (x – 3)

 f (x) = 0 gives x = 1, 3

Let us observe the sign of f(x)

x – 0 3 

The sign of
– ve + ve + ve +ve
f(x)

There are three variations of signs of f(x) and hence the equation f(x) = 0 has all roots real (three real roots)

3. Answer (4)

We have f(x) = x4 – 8x3 + 22x2 – 24x + 20

 f(x) = 4x3 – 24x2 + 44x – 24

= 4 (x3 – 6x2 + 11x – 6)

= 4 (x – 1) (x – 2) (x – 3)

 f(x) = 0 gives x = 1, 2, 3.

Let us observe the sign of f(x)

X – 1 2 3 

The sign of
– ve + ve + ve + ve + ve
f(x)

Here no variation of sign of f(x) takes place and hence the given equation f(x) = 0 has no real root.

C6. 1. Answer (1)

2. Answer (4)
3. Answer (2) (5, 24)

A rough sketch of the given function


y

⎧ 6, x2

f(x) = ⎨ 6 x – 6 2  x5
⎪34 – 2 x x5 x
⎩ 0 1 5

is as follows :

Clearly the graph intersects x-axis in one point, hence the number of real root of f(x) = 0 is 1. For f(x) = 6,
the branch of curve coincides with x-axis hence f(x) = 6 has infinites many solutions. When f(x) = –2008 the
number solution of positive value of x is one.

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 781
C7. 1. Answer (1)
The number of ways of selecting one or more fruits
= 6 × 8 × 10 – 1 = 479
2. Answer (2)
The number of possible combination of dyes under given condition
= (23) (24 – 1) (25 – 1) = 3720
3. Answer (3)
The required number of ways
= 24 × 4 × 25 – 1 = 2047
C8. 1. Answer (1)
Let us divide the square into 16 unit squares as given in the figure. Out of 17 points distributed in the
big square, atleast one of the small squares must have at least two points by Pigeon hole principle. These
two points being on a unit square are at the most 2 units distance apart as 2 is the length of the
diagonal of the unit square.

2. Answer (1)
Let ABCDEF be the regular hexagon of side 2 cm and P,Q,R,S, T, U are respectively the midpoints of
the sides AB, BC, CD, DE, EF as FA. Let us join the opposite vertices so that we get in all 24 equilateral
triangles of side 1 cm.

E S D
11 9
T 12 10 8
R
13 21 7
14 22 6
20
F C
15 23 19
5
16 18 4
U 17 24 3 Q
1 2
A P B

We have 25 points, so of these 25 points inside the hexagon ABCDEF, atleast 2 points lie inside and one
of the triangle whose sides are 1 cm long, hence at least two points among them will be 1 cm apart.
3. Answer (1)

100 – 1
These are  1  34 elements in the progression 1, 4, 7, ..., 100 Let us consider the following
3
49 – 4
pairs (4,100), (7, 97) (10, 94), ....(49, 55) There are in all  1 = 16 pairs. Use PHP.
3
Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
782 Brain Storming Comprehensions Success Magnet (Solutions)

C9. 1. Answer (3)


dy
Slope of the tangent at any point p(x, y) is y
dx
dy
  cy
dx
 y = ec(x–1)
Since x + ky = 1 + k is normal at (1, 1)
 k = 1,
Hence y = f(x) = ek(x – 1)
2. Answer (4)
⎛ dy ⎞
Slope of the tangent is B (0, e– k) is ⎜ dx ⎟ = ke–k
⎝ ⎠B
 y – e = ke (x)
–k –k

 y = e–k (kx + 1)
3. Answer (3)
Area bounded
1
⎛1 x k  x – 1 ⎞
= ∫ ⎜⎝ k – k  i – e ⎟ dx

0

1⎛ 1 ⎞
= ⎜ k –  e –k ⎟
k ⎝ 2 ⎠
C10. 1. Answer (1)
2. Answer (1)
3. Answer (3)
The equation of the tangent to the given conic is

y – 1 = mx  m 2 – 1

Which will pass through origin provided – 1 = ± m 2 – 1


 m2 = 2

m=  2
(p,q)
m=– 2 for negative slope.
q
But slope of the tangent = = – 2
p (–1, 1) (1, 1)
p 1 x x
 q 
2 – 2, 0 (0, 0) 2, 0

⎛p⎞ ⎛ 1 ⎞ 3
 cos –1 ⎜⎜ ⎟⎟ = cos –1 ⎜⎜ – ⎟⎟ =
q
⎝ ⎠ ⎝ 2⎠ 4

⎛p⎞
sin –1 ⎜⎜ ⎟⎟ = sin –1 ⎛⎜  1 ⎞⎟ = – 
⎝q⎠ ⎜ ⎟ 4
⎝ 2⎠

2b
Length of latus rectum = = 2a = 2
a

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 783
C11. 1. Answer (2)
2. Answer (3)
3. Answer (2)
The two parabolas y2 = 4pn x and y2 = 4pn (pn – x)

⎛ pn ⎞ ⎛p ⎞
intersect each other at ⎜ , 2 pn ⎟ and ⎜ n – 2 pn ⎟
⎝ 2 ⎠ ⎝ 2 ⎠
An = Area enclose between the parabolas

⎡ pn ⎤
⎢ 2 1 pn 1 ⎥ (0, 0) (pn, 0)
= 2 ⎢2 pn . x dx  2 pn . pn – x  dx ⎥⎥
2
⎢ ∫ 2

⎢ 0 pn ⎥
⎢⎣ 2 ⎥⎦ (pn/2,p2 pn)

⎡2 2 2 2⎤ 1 16 2 1 4 2 2
= 4 ⎢ . pn  pn ⎥ = 3 pn = pn
⎣ 3 3 ⎦ 2 2 2 2 3
Since p1, p2, p3..., pn are in G.P.

 p12 , p22 , p32 , ..., pn2 , ... are also in G.P.

4 2 2 4 2 4 2 2 4 2 2
 p , p22 , p3 ,...., pn are in G.P.
3 1 3 3 3
 A1, A2, A3, .., An are in G.P.
The sum of areas when n  
A1 + A2 + A3 + ... + ...

4 2 2 4 2 2
p1 .1
3 3
= = 1
⎛ p2 ⎞ 1–
1 – ⎜ 22 ⎟ 2
⎜p ⎟
⎝ 1 ⎠
8 2
= sq. units
3
The distances between directrices of the parabolas = distance between (x + pn = 0) and (x – 2pn = 0) = 3pn
 d1, d2, d3, ..., dn, ... are in G.P.
C12. 1. Answer (1)
The given functional realtion is f(x) + f(2x) + f(1 + x) + f(2 – x) = 0
 f(0) + f(0) + f(1) + f(2) = 0 for x = 0
 f(1) + f(2) + 2f(0) = 0
Also for x = 1, f(1) + f(2) + f(2) + f(1) = 1
 2f(1) + 2f(2) = 1
1
 f(1) + f(2) =
2
Substituting the value of f(1) + f(2), we get
1
2f(0) + =0
2
1
 f(0) = –
4
Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
784 Brain Storming Comprehensions Success Magnet (Solutions)

2. Answer (3)

From the given relation we have

(x + 1)2 + (y + 1)2 + (z + 1)2 + (t + 1)2 = 4(x + y + z + t)

 (x + 1)2 – 4x + (y + 1)2 – 4y + (z + 1)2 – 4z + (t + 1)2 – 4t = 0

 (x – 1)2 + (y – 1)2 + (z – 1)2 + (t – 1)2 = 0

Which holds iff x = y = z = t = 1

⎛ 1 ⎞⎛ 1 ⎞⎛ 1 ⎞⎛ 1 ⎞
Thus ⎜⎜ x  – 1⎟⎟ ⎜ y  – 1⎟ ⎜ z  – 1⎟ ⎜ t  – 1⎟ = 1
⎝ y ⎠⎝ z ⎠⎝ t ⎠⎝ x ⎠

3. Answer (1)

We have

⎛ 1 ⎞
3f (x + 2009) + 4f ⎜⎜ ⎟⎟ = 4x
⎝ x  2009 ⎠

⎛ 1⎞
 3f x   4f ⎜ ⎟ = 4(x – 2009)
⎝x⎠

⎛ 1⎞ ⎛1 ⎞
and 4f(x) + 3f ⎜ ⎟ = 4 ⎜ – 2009 ⎟
⎝x⎠ ⎝ x ⎠

4
 7f(x) = 4 ⎡⎢ – 4  2009 – 3 x  2009  3⎤⎥
⎣x ⎦

⎡4 ⎤
= 4 ⎢ – 3 x – 2009 ⎥
⎣x ⎦

4 ⎡ 4 ⎤
 f(2009) =
7 ⎢ 2009 – 4  2009 ⎥
⎣ ⎦

16 2009  – 1
2
16 ⎛ 2008.2010 ⎞
= – – ⎜ ⎟
7 2009 7 ⎝ 2009 ⎠

C13. 1. Answer (4)

x 2 1  x 

We have ∫ f t dt
0
=x

Differentiating it w.r.t. x we get

f(x2 + x3) . (2x + 3x2) = 1

1
 f(2) =
5

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 785
2. Answer (3)
We have

1
g(1) = 5 and ∫ g t dt
0
=2

x
1
∫ x – t  g t  dt
2
f(x) = 2
0

x
1
 f (x) = 2 x – t  g t dt  0

2
0

 f (x) = g t  dt  0

0

and f (x) = g(x)

1
Thus f (1) = g(1) = 5 and f (1) =
∫ g t  dt
0
=2

 f (1) – f (1) = 5 – 2 = 3
3. Answer (3)
We have

x 1
2t ⎛ 2 ⎞
g(x) = xke2x and f(x) = ∫ e ⎜ 3t  1⎟ 2 dt
⎝ ⎠
0

 g (x) = kxk–1e2x + 2xk e2x = e2x xk–1 (2x + k)

 
1
2x 2
and f (x) = e 3 x  1 2

 
1
f  x  e2x 3x 2  1 2
Now xlim
  g x 
= lim 2 x k –1
x e . x 2 x  k 

1
⎛ 1 ⎞2
x ⎜3  2 ⎟
= lim ⎝ x ⎠
x ⎛ k⎞
xk ⎜2  ⎟
⎝ x⎠

Which will be finite and non-zero when k = 1 and in the case

f x  3
lim
g x 
x 
=
2

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
786 Brain Storming Comprehensions Success Magnet (Solutions)

C14. 1. Answer (2)


Two curves are symmetrical about both axes and intersect in four points, so the circle through their points
of intersection will have centre at origin.

x2 y2
Solving x2 – y2 = 0 as  = 1, We get
a2 b2
a 2b 2
x2 = y2 =
a2  b2

2a 2 b 2 2 ab
 radius of the circle = =
a2  b2 a  b2
2

2. Answer (3)
Let the eccentric angle of S be . We know that the sum of eccentric angles of four concyclic points of
the elipse is even multiple of 


  +         = 2n
2

3
  = 2 – – 3
2


= – 3
2
3. Answer (3)
The equation of the curve through the point of intersection of the given curves is
x2 + y2 – 4x – 5 +  (x2 + y2 – 1) = 0
 (1 + )x2 + (1 + ) y2 – 4x – (5 + ) y = 0
which will represent a pair of straight lines if
– (1 + ) [(1 + ) (5 + ) + 0 – (1 + ) . 0 – (1 + ) .4 + 0 = 0
 (1 + ) [(5 + ) (1 + ) + 4] = 0
 (1 + ) [2 + 6 + 9] = 0
 (1 + ) ( + 3)2 = 0
 = – 1, – 3
Hence, two pairs of straight lines can be drawn.
C15. 1. Answer (3)
We have
a2008 + b2008 + 2006 = 2008ab

2008
 a  b 2008  1  1  1  .....  1 2008 2008 2008 2006
 a b 1 = |a| |b|
2008

 a2008 + b2008 + 2006  2008ab


By hypothesis, equalitis holds only when all the 2008 terms are equal i.e. a2008 = b2008 = 1
 a = ± 1, b = ± 1 is the solution set.

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 787
2. Answer (1)

From the given condition

c a
–1 a b – 1
ab –1
bc c = 5 = 5 × 1 × 1; 5 is a prime number. Hence the different possibilities are either
c a b c a b c a b
ab –1
 5, b c –1
 1, c a –1
 1 or a b –1 = 1, b c –1
 5 , c a –1 = 1 and a b –1 = 1, b c –1 = 1 c a –1 = 5.

Hence either a = 5, b = 2, c = 1 or a = 1, b = 5, c = 1 or c = 5, a = 2, b = 1

3. Answer (2)

We observe that

– 5  3cos – 4sin 5, R

Hence 6 – 3cos + 4sin > 0

and 7 + 3cos – 4sin > 0

Also (6 – 3cos + 4 sinq) + (7 + 3cos – 4sin) = 13

Thus (6 – 3cos + 4sin)7 (7 + 3cos – 4sin)6  7766.

C16. 1. Answer (1)

2. Answer (4)

3. Answer (3)

Any matrix of order (n – 1) × (n – 1) can be formed using entries as 1 or – 1 in 2 n – 12 different ways.
Now the nth row and the nth column can be filled by unique method keeping in mind the product of members
of the each row and column is –1

For n = 3, the no. of possible matrices = 2 3 – 1 = 24 = 16


2

For n = 4 , the number of possible matrices = 2(4–1)2 = 29 = 512

Also 2 n – 1  10000
2

 least value of n is 5

C17. 1. Answer (2)

2. Answer (3)

3. Answer (4)

Let us consider the cubic equation

3 + x2 + y + z = 0

Clearly a, b, c are roots of the equation.

Hence a + b + c = – x

ab + bc + ca = y

abc = – z

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
788 Brain Storming Comprehensions Success Magnet (Solutions)

C18. 1. Answer (4)


2. Answer (2)
3. Answer (3)
Let 1, 1 ; 2, 2; 3, 3 be the roots after given equations ax2 – 2bx + c = 0, bx2 – 2cx + a = 0 and
cx2 – 2ax + b = 0 respectively, Then

2b c
1 + 1 = , 11 =
b a

2c a
2 + 2 = , 22 =
a b

2a b
3 + 3 = , 33 =
c c

From A.M. – G.M inequality

⎛ 1  1 ⎞ ⎛  2   2 ⎞ ⎛  3   3 ⎞ 1
⎜ ⎟⎜ ⎟⎜ ⎟  11   2 2   33 2
⎝ 2 ⎠⎝ 2 ⎠⎝ 2 ⎠

1
b c a ⎛ c a b ⎞2
   ⎜   ⎟
a a c ⎝a b c ⎠

11
Equality holds
We know that equality of AM – GM inequalities holds iff numbers are equal
i.e 1 = 1, 2 = 2, 3 = 3
a=b=c
 ax2 + bx + c = 0
 x2 + x + 1 = 0 has no real root.
Also b2 + c2 = 22 + 22 = 8
and a3 + b3 + c3 – 3abc = 3a3 – 3a3 = 0
C19. 1. Answer (4)
2. Answer (1)
3. Answer (3)
We have

1
f(i, i + 1) =
3

and f(i, j) = f(i, k) + f(k, j) – 2f(i, k) f(k, j)


 f(i, j) = f(i, j – 1) + f(j –1, j) – 2f (i, j –1) f(j –1, j)

1 2
= f(i, j –1) + – f i , j  1
3 3
1 1
=  f i , j  1
3 3

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 789

2 2
1 ⎛ 1⎞ ⎛ 1⎞
=  ⎜ ⎟  ⎜ ⎟ f i , j  2
3 ⎝3⎠ ⎝3⎠

2 3  j – 1
1 ⎛ 1⎞ ⎛ 1⎞ ⎛ 1⎞
=  ⎜ ⎟  ⎜ ⎟  ...  ⎜ ⎟
3 ⎝3⎠ 3
⎝ ⎠ ⎝3⎠

⎧⎪ ⎛ 1 ⎞ j – 1 ⎫⎪
⎨1 – ⎜ ⎟ ⎬
1 ⎪⎩ ⎝ 3 ⎠ ⎪⎭
= 1
3
1–
3

1 ⎧⎪ ⎛ 1 ⎞ j – i ⎫⎪
= 2 ⎨1 – ⎜ ⎟ ⎬
⎪⎩ ⎝ 3 ⎠ ⎪⎭

1
 lim f(1, n) =
n 2
C20. 1. Answer (1)
2. Answer (1)
3. Answer (3)
We have
1

f(x) = ∫t–x
0
tdt

⎧1
⎪ (t  x )t dt ,
⎪ ∫ x0
⎪0
⎪x 1

∫ ∫
= ⎨ ( x  t )t dt  (t  x )t dt , 0  x  1
⎪0 x
⎪1

⎪⎩0

⎪ ( x  t ) t dt , x 1

⎧ 1 x
⎪ 3 – 2, x0
⎪ 3
⎪x x 1
= ⎨ –  , 0  x 1
⎪ 3 2 3
⎪ x – 1, 1 x
⎪ 2 3

Clearly f(x) is continuous everywhere and its graph doesnot cross x-axis. For the least value we have
1
f(x) = x2 – =0
2

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
790 Brain Storming Comprehensions Success Magnet (Solutions)

1
x= in (0, 1)
2

1
f (x) = 2x which is + ve at x =
2

2 –1
and f(x)min =
3 2

C21. 1. Answer (3)


2. Answer (1)
3. Answer (2)

Let p(x) = ∫ f x dx


 p(x) is a polynomial of degree 21 as f(x) is a polynomial of degree 20.
 p(x) is continuous and differentiable for all xR

i 1

Also ∫ f x  dx
i
= p(i + 1) – p(i) = 0 (Given)  i satisfying 0  i  19

 p(i + 1) = p(i)
 Rolle’s theorem is applicable.

 p(x) = f(x) = 0 has atleast one root in (i, i + 1),  0  i  19

There are 20 such intervals and hence. f(x) = 0 has at least 20 real roots. But f(x) is a polynomial of degree
20, hence f(x) = 0 has exactly 20 distinct real roots each in [i, i + 1],  i [0, 19]
Moreover

g(x) = f x 2  f x f x 

d
= (f ( x ) f  ( x ))
dx

 g(x) = 0 gives f(x) f (x) = as constant


C22. 1. Answer (2)
Let the radius of the circles be r.

C C2
C1

then CC1 = r1 – r

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456
Success Magnet (Solutions) Brain Storming Comprehensions 791

CC2 = r + r2
CC1 + CC2 = r1 + r2 = constant
 locus of C is an ellipse
2. Answer (3)
CC1 = r + r1
CC2 = r + r2
 CC1 – CC2 = r1 – r2 = constant

C1 C

C2

 Locus of C is a hyperbola
3. Answer (4)
If r1 = r2 , then CC1 = CC2

C
C1
C2

  

Aakash Educational Services Pvt. Ltd. Regd. Office : Aakash Tower, 8, Pusa Road, New Delhi-110005 Ph.011-47623456